2007
DOI: 10.1371/journal.pbio.0050078
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Play a Key Role in Circadian Cell Cycle Rhythms

Abstract: Clock output pathways play a pivotal role by relaying timing information from the circadian clock to a diversity of physiological systems. Both cell-autonomous and systemic mechanisms have been implicated as clock outputs; however, the relative importance and interplay between these mechanisms are poorly understood. The cell cycle represents a highly conserved regulatory target of the circadian timing system. Previously, we have demonstrated that in zebrafish, the circadian clock has the capacity to generate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 66 publications
3
108
1
Order By: Relevance
“…Molecular clocks in healthy cells control the cell division cycle through Clock:Bmal1 regulation of several key cell cycle genes (Fu and Lee 2003;Matsuo et al 2003). Circadian physiology can also and redundantly regulate cell cycle traverse (Dickmeis et al 2007).…”
Section: A Hypothetical Model Of the Interactions Between Circadian Tmentioning
confidence: 99%
“…Molecular clocks in healthy cells control the cell division cycle through Clock:Bmal1 regulation of several key cell cycle genes (Fu and Lee 2003;Matsuo et al 2003). Circadian physiology can also and redundantly regulate cell cycle traverse (Dickmeis et al 2007).…”
Section: A Hypothetical Model Of the Interactions Between Circadian Tmentioning
confidence: 99%
“…Independent circadian clocks are found in virtually all zebrafish tissues, and these tissues are themselves directly light responsive 18,19 . Light signals have a strong impact, not only on resetting of the zebrafish circadian clock [20][21][22] , but also on numerous aspects of zebrafish cell biology, such as the activation of DNA repair processes [23][24][25][26] and the regulation of cell cycle events [27][28][29][30] . Evolving in a completely dark environment is therefore likely to impact fish physiology in a dramatic manner.…”
mentioning
confidence: 99%
“…Our own studies have revealed a role for glucocorticoids in the regulation of circadian rhythms of cell proliferation in zebrafish larvae [161]. Circadian cell cycle rhythms can be observed both in larvae and in zebrafish-derived cell lines, implying that cell-autonomous clock regulation also exists in this species [162].…”
Section: Glucocorticoids and Rhythms Of Cell Proliferationmentioning
confidence: 89%
“…Circadian cell cycle rhythms can be observed both in larvae and in zebrafish-derived cell lines, implying that cell-autonomous clock regulation also exists in this species [162]. However, in vivo, systemic input is also required: in mutants lacking a pituitary gland, cell cycle rhythms are severely attenuated [161]. Subsequent analysis of mutants that lack subsets of the pituitary cell types identified the corticotrope lineage as the source for the required signal.…”
Section: Glucocorticoids and Rhythms Of Cell Proliferationmentioning
confidence: 99%
See 1 more Smart Citation